(untitled) (Journal of Applied Learning and Teaching, 2025)
The concept of digitalised curricula for the Fourth Industrial Revolution (4IR) is an exciting and evolving topic. Moving into the 4IR, the focus is on integrating advanced technologies like artificial intelligence (AI), machine learning (ML), robotics, and the Internet of Things (IoT) into higher education (HE) to create more personalised, efficient, and adaptive student learning experiences. 4IR has changed the pedagogical narratives from personalised learning to AI examinations in HE. This qualitative study explores the experiences of academics harnessing to digitalise curricula who participated in the online AI literacy training sessions on Generative AI (GenAI) tools at an open distance e-learning university (ODeL). Semi-structured online interviews were used to examine the views of participants. A purposive sampling of eight academics was interviewed on Microsoft Teams as a virtual platform. The transcribed data were uploaded and analysed using the computerised qualitative data software NVivo 14.0, and themes were identified. Findings reported that academics used GenAI-powered tools to create educational content for individual learning styles and paces for any course. Furthermore, virtual and augmented reality can create immersive learning environments for active student participation. Moreover, offering online learning options to accommodate diverse student needs was highlighted. To digitalise curricula, academics must be reskilled with AI literacy and other professional development sessions in critical thinking, problem-solving, and digital literacy to prepare students for future teaching professions. Participants facilitate collaboration through digital platforms (Moodle LMS), allowing students to work in team-based learning sessions. Finally, participants expressed concerns about the digital divide, data privacy, and ethics of using AI in digitalised curricula.